2018
DOI: 10.1002/jcb.27031
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA PlncRNA‐1 promotes cell proliferation and hepatic metastasis in colorectal cancer

Abstract: Emerging evidence has identified that long non-coding RNAs (lncRNAs) may play an important role in the pathogenesis of many cancer types, including colorectal cancer (CRC). However, the role of PlncRNA-1 in CRC remains unclear. The aim of our present study was to investigate the potential functions of PlncRNA-1 in CRC and to identify the underlying mechanisms of action. We demonstrated that up-regulated PlncRNA-1 in CRC tissues and cells promoted cell proliferation by accelerating cell cycle process and inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
(72 reference statements)
0
14
0
Order By: Relevance
“…Thirty-one studies demonstrated that increased lncRNA expression was associated with increased cellular proliferation in vitro. 37,38,[40][41][42][43][44][45]49,50,54,58,59,[61][62][63][65][66][67]69,72,73,77,79,80,83,84,[86][87][88][89][90][94][95][96][97] In contrast, decreased expression of four lncRNAs was associated with increased cellular proliferation. 46,68,75,85…”
Section: Cell Proliferationmentioning
confidence: 99%
“…Thirty-one studies demonstrated that increased lncRNA expression was associated with increased cellular proliferation in vitro. 37,38,[40][41][42][43][44][45]49,50,54,58,59,[61][62][63][65][66][67]69,72,73,77,79,80,83,84,[86][87][88][89][90][94][95][96][97] In contrast, decreased expression of four lncRNAs was associated with increased cellular proliferation. 46,68,75,85…”
Section: Cell Proliferationmentioning
confidence: 99%
“…LncRNAs have become a hot topic as diagnostic markers of diseases. The transcriptional level of PlncRNA-1 is signi cantly elevated in multiple malignancies, and PlncRNA-1 acts as a transcriptional regulator of various developmental processes [17][18][19][20][21][22][23][24][25]. In several human tumours, overexpression of PlncRNA-1 is related to poor OS, high TNM classi cation, advanced clinical stage, low histological differentiation, and poor vital status [20,22,24,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…PlncRNA-1 is ubiquitously expressed in the prostate, salivary glands and 25 other tissues. It has been shown that PlncRNA-1 plays an important role in various cancer types, including prostate cancer, colorectal cancer, osteosarcoma, glioma and oesophageal squamous carcinoma [17][18][19][20][21][22][23][24][25][26]. Accumulating evidence has demonstrated that PlncRNA-1 acts as a transcriptional regulator to modify various developmental processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PlncRNA-1 targets β-catenin through a competitive endogenous RNA mechanism with miR-204 to mediate EMT. 77 In contrast, H19 and TUG1 target β-catenin indirectly by targeting molecules that interact with β-catenin. 66,[78][79][80] H19 targets PGRN and TUG1 targets KIAA1199, through miR-29b binding and miR-600 binding respectively.…”
Section: Wnt/β-catenin Signalingmentioning
confidence: 99%